Tuma'ninah dalam Salat dan Teori Flow: Studi Psikologis Al-Qur'an tentang Ketenangan Hati dan Kesehatan Mental - Muh Adnan; Yusuf Rahman; Basri Mahmud; Dewi Sartika (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to examine the concept of ṭumaʼnīnah in prayer based on the perspective of the Qur’an and its relevance to peace of mind and mental health. This study uses a qualitative approach based on literature research, namely collecting verses from the Qur’an related to ṭumaʼnīnah, zikr, and peace of mind, these verses are analyzed using the tahlili method, by examining various perspectives of classical and contemporary exegesis from linguistic, theological, and contextual points of view, then relating them to Mihaly Csikszentmihalyi’s psychological theory which developed the theory of flow. The results show that tuma’ninah in the Qur’an is closely related to the concept of peace of mind (nafs al-muṭma’innah), which is grounded in faith, zikir, gratitude, and belief in Allah’s help. Prayer performed with devotion and tuma’ninah not only improves the quality of worship but also acts as spiritual therapy that can reduce stress, anxiety, and mental disorders. This research is significant for the development of Islamic psychology, as it shows that the concept of ṭumaʼnīnah in the Qur’an, as practiced in prayer, is not merely ritualistic but also has psychological implications relevant to peace of mind and human mental health.